Microstructure and mechanical behavior of functionally graded Al A359/SiCp composite - Rodríguez-Castro, R; Wetherhold, RC; Kelestemur, MH (Elsevier Science Sa, 2002)
The microstructure and mechanical behavior including tensile and fracture properties of a. functionally gradient Al A359/SiCp composite processed by centrifugal casting have been investigated. The particle volume fraction and, therefore, elasticity modulus was gradually changed in the continuous form along a certain direction by using the centrifugal casting. The effect of SiC particulate reinforcement on strengthening of A359 Al alloy was experimentally studied by tensile testing specimens with different SiC contents. There was a continuous increase in tensile and yield strength with increasing SiC volume, fractions in the range of 0.20-0.30. On the contrary, there was a reduction in tensile and yield strength for SiC concentrations in the range of 0.30-0.40. The fracture experiments were performed according to the ASTM E399 standards. Single edge cracked plate tension (SECT) and single edge cracked four point bending (4PB) specimens, which are taken, from rectangular Al/SiCp blocks, were used for fracture tests. The fracture toughness, K-1C, and fractographic characteristics of the material were determined by using MTS 810 servohydraulic machine and Hitachi S-800 scanning electron microscopy (SEM), respectively. At elevated SiC concentrations (low values of crack length), limited dissipation of energy by restrained plastic deformation of the matrix at the crack tip produced low fracture toughness values. On the contrary, at longer crack. lengths SiC content decreased and there was more absorption of energy, resulting in higher fracture toughness values. A ductile failure process of void coalescence type fracture in the matrix of the composite was observed but the void size was less when the SiC concentration was higher. In addition, SEM fractographs also displayed that fracture and de-cohesion of SiC occurred with particle fracture dominating over de-cohesion and with fracture incidence increasing as particle concentration increases. (C) 2002 Elsevier Science BN. All rights reserved.
Keywords: Al/SiCp composites; functionally graded material; microstructure; fracture mechanics behavior